2020
DOI: 10.1002/cam4.3603
|View full text |Cite
|
Sign up to set email alerts
|

Associations between genetic variants of KIF5B, FMN1, and MGAT3 in the cadherin pathway and pancreatic cancer risk

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Not only have formin levels been associated with cancer prognosis, but gene variants and deletions have also been associated with the risk of cancer progression. For example, specific FMN1 variants have been linked to a higher risk of developing pancreatic [300] and prostate cancer [304]. In lung cancer, a variant in the FH2 domain of DAAM2 (p.Asp762Gly) has been associated with a protective effect, and, although not a statistically significant result, a variant in the DID (p.Arg172His) was found to be enriched in healthy controls [292].…”
Section: Formins As Prognostic Biomarkers and Therapeutical Targets In Cancermentioning
confidence: 99%
“…Not only have formin levels been associated with cancer prognosis, but gene variants and deletions have also been associated with the risk of cancer progression. For example, specific FMN1 variants have been linked to a higher risk of developing pancreatic [300] and prostate cancer [304]. In lung cancer, a variant in the FH2 domain of DAAM2 (p.Asp762Gly) has been associated with a protective effect, and, although not a statistically significant result, a variant in the DID (p.Arg172His) was found to be enriched in healthy controls [292].…”
Section: Formins As Prognostic Biomarkers and Therapeutical Targets In Cancermentioning
confidence: 99%
“…It was imperative to investigate if the EVs that were injected into the mice could in uence any biological activity. Several studies [67][68][69][70] have shown that there is a distinct pancreatic microbiome which could decisively in uence the development of pancreatic cancer. To investigate this phenomenon, fecal pellets were collected from mice who were injected with PBS control or with EVs from KPC, PSC and co-culture conditions two weeks after education.…”
Section: Discussionmentioning
confidence: 99%
“…Its mutation, regulating filamin expression and neuronal migration [ 7 ], was detected in breast neuroendocrine neoplasms (NENs), a peculiar histologic subtype [ 93 ]. Genome-wide sequencing shows that MAP3K4 and its mutations also frequently appear in several kinds of tumor tissues, such as serous endometrial tumor [ 94 ], wilms tumor [ 95 ], EBV-positive gastric tumor [ 96 ], pancreatic cancer [ 97 ], and family lung cancer [ 98 ].…”
Section: The Complex Function Of Map3k4 Concerning Tumormentioning
confidence: 99%